A nanotechnology-based new approach in the treatment of breast cancer: Biosynthesized silver nanoparticles using Cuminum cyminum L. seed extract - Dinparvar, Sahar; Bagirova, Melahat; Allahverdiyev, Adil M.; Abamor, Emrah Sefik; Safarov, Tural; Aydogdu, Mehmet; Aktas, Didem (ELSEVIER SCIENCE SA, 2020)
The present study reports the anticancer activities of Cuminum cyminum L. (Cumin) seed extract, chemically synthetized silver nanoparticles (AgNPs) and biosynthesized silver nanoparticles (Bio-AgNPs) from Cumin seeds on human breast adenocarcinoma cell line (MCF-7) and human breast adenocarcinoma metastatic cell line (AU565). The synthetized nanoparticles were characterized by dynamic light scattering (DLS), UV-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The cytotoxic and anticancer effects of AgNPs and Bio-AgNPs were determined by MTT assay. According to the cytotoxicity analysis, Bio-AgNPs appears to be less toxic against J774 macrophage cells than AgNPs since IC50, values were measured as 0.75 and 1.25 mu g/ml for AgNPs and Bio-AgNPs, respectively. On the other hand, Bio-AgNPs demonstrated significant inhibitory effects on human breast cancer cells at non-toxic concentrations such as 0.25 and 0.5 mu g/ml. However, at increased concentrations, the lethal effects of AgNPs on breast cancer cells were higher than Bio-AgNPs. When cytotoxic and anticancer characteristics of Cumin extract were investigated, it was established that it did not show any inhibitory effect on J774 cells, while killing the half of MCF-7 cells at investigated concentrations. Interestingly, Cumin extract gave rise to no inhibitory effects against AU565 cells. On the other hand, AgNPs and Bio-AgNPs exhibited considerable anticancer activities on both cell lines. The inhibition percentages of AgNPs on MCF-7 and AU565 cell lines were respectively evaluated as 95% and 97% at the highest concentrations applied (12.5 mu g/ml). Similarly, we determined that 87.5% and 96% of MCF-7 and AU565 cells were respectively inhibited when they were exposed to the highest concentrations of Bio-AgNPs. Considering relatively toxic-free features of Bio-AgNPs prepared from Cuminum cyminum L. seed extracts, it can be thought that this formulation will be a pioneer in development of nanotechnology-based new anticancer drug for the treatment of breast cancer in near future.
Keywords: Silver nanoparticles; Cuminum cyminum L.; Biogenic synthesis; Bionanotechnology; Anticancer activity; GREEN SYNTHESIS; MEDIATED SYNTHESIS; ANTIBACTERIAL ACTIVITY; GOLD NANOPARTICLES; LEAF EXTRACT; IN-VITRO; OPTIMIZATION; NANOMATERIALS; CYTOTOXICITY; Biochemistry & Molecular Biology; Biophysics